2023
DOI: 10.3762/bjoc.19.110
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 5-arylidenerhodanines in L-proline-based deep eutectic solvent

Stéphanie Hesse

Abstract: Rhodanines and their derivatives are known to have many pharmacological activities that can be modulated through different functionalization sites. One of the most studied modification in those scaffolds is the introduction of a benzylidene moiety on C5 via a Knoevenagel reaction. Here, a facile synthesis of 5-arylidenerhodanines via a Knoevenagel reaction in an ʟ-proline-based deep eutectic solvent (DES) is reported. This method is fast (1 h at 60 °C), easy, catalyst-free and sustainable as no classical organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…First, we used the conditions developed for rhodanine condensation with aldehydes (i.e., 0.8 g Proline:Glycerol (1:2), 0.5 mmole of aldehyde and 0.5 mmole of rhodanine, heating at 60°C for 1 h) [20] and applied them to rhodanine‐3‐acetic acid (Table 1). One more time, we do not use any volatile solvent as the reaction workup involved addition of water for separating the crude product from the aqueous phase containing the DES.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, we used the conditions developed for rhodanine condensation with aldehydes (i.e., 0.8 g Proline:Glycerol (1:2), 0.5 mmole of aldehyde and 0.5 mmole of rhodanine, heating at 60°C for 1 h) [20] and applied them to rhodanine‐3‐acetic acid (Table 1). One more time, we do not use any volatile solvent as the reaction workup involved addition of water for separating the crude product from the aqueous phase containing the DES.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 1a-7a are described in Reference [20]. [33,36] Yellow solid obtained after 1 h at 60 C in 72% yield (117 mg).…”
Section: General Procedures For the Knoevenagel Condensationmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study carried out by Hesse [ 96 ] reported the preparation of rhodanine derivatives via Knoevenagel condensation using the eutectic system ChCl:U (1:2). The author was inspired by others’ work, where L-proline-based DESs were used as reaction media in Knoevenagel condensations for the synthesis of other classes of compounds.…”
Section: Deep Eutectic Systemsmentioning
confidence: 99%
“…Arylidene-functionalized rhodanines were also recently screened to evaluate their anticancer activity against several cancer cell lines [19,20] or their propensity as antibacterial, antifungal or antioxidants agents [21][22][23]. In this context, we have reacted a series of 4-arylidene-5-thioxo-thiazolidin-2-ones with the secondary cyclic amine tetrahydroisoquinoline (THIQ) to convert them to (Z)-5-ylidene-2-aminothiazol-4(5H)-ones [18].…”
Section: Introductionmentioning
confidence: 99%